Bergson e o eu dividido - Ribeiro, Eduardo Soares (2014)
This work is aimed at investigating the inner life in Bergson s first book, Time and Free Will An essay on the immediate data of consciousness (1889). We try to analyze especially the notions of duration and space in light of what we call the divided self , i.e., the division established by Bergson between the superficial self related to space, social life and language and the deap-seated self which concerns the pure duration of consciousness, the continuous multiplicity of interpenetration of psychological states and creating and unpredictability that constitutes each free act. At the end, and already in possession of the conclusions on the Essay, we will discuss the bergsonian intuitive method and its relationship with the divided self.